DEKOMPOSISI TRADED SPREAD SAHAM DI BURSA EFEK INDONESIA: ORDER PROCESSING COST, INVENTORY HOLDING COST, DAN ADVERSE SELECTION COST - Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2016)
Stock market performance can be viewed from various aspects. One of this aspect is the amount of traded spread. The greater of traded spread can be caused by a lack of trading system and disclosure. Therefore, the decomposition of traded spread is important for the study. This research was conducted to develop a model of traded spread and prove that: the order processing cost, inventory holding cost, and adverse selection cost are the component of traded spread. To achieve these objectives, the stock price and order flow observed during the years 2007 - 2008 and using the purposive sampling as the sampling technique. Samples were observed at 1.782 and using trade indicators to determine whether the transactions undertaken based on the ask price or bid price. The data were analyzed using the multiple regression. The research indicated that: First, the model of traded spread can be used to explain the decomposition of traded spread. Second, the contribution of order processing cost is 29 per cent, the contribution of inventory holding cost is 68 per cent, and the contribution of adverse selection cost is 3 percent. Third, the contribution of adverse selection cost is relatively low when compared with the contribution of real spread. Furthermore, the results of this study can be used to determine the policies in reducing of traded spread.